Endovenous laser ablation of great saphenous vein and pharmacotherapy of acute ascending thrombophlebitis: results of a three-month follow-up - K. A. Kaperiz; A. O. Rastatueva; I. S. Yavelov; O. M. Drapkina (Столичная издательская компания, 2023)
Aim. In patients with acute ascending thrombophlebitis of the great saphenous vein and/or its large tributaries, assess the incidence of venous thrombosis progression over 3 months with 1,5-month fondaparinux sodium therapy and endovenous laser ablation of the saphenofemoral junction in combination with short-term (7-day) anticoagulant therapy or without anticoagulation.Material and methods. This single-center, prospective, randomized, open-label study included data from 91 patients with acute ascending thrombophlebitis of the great saphenous vein and/or its large tributaries, of which 30 were in the group of endovenous laser ablation without anticoagulation, 32 - in the group of endovenous laser ablation in combination with 7-day fondaparinux therapy, and 29 - in the 1,5-month fondaparinux therapy group. Venous thrombosis progression rate within 90±2 days was assessed. Compression ultrasonography of lower limb veins was performed on days 7±2, 45±2 and 90±2 after randomization, as well as in case of thrombosis progression suspicion.Results. The mean age of patients was 49,4±14,2 years. There were more women (73,6%). There was a low prevalence of risk factors for the development and progression of venous thrombosis: obesity - 6,6%, type 2 diabetes - in 2 patients, class 2 heart failure - in 1, autoimmune disease (scleroderma in remission) - in 1, prior cancer - in 1. Previous episodes of thrombophlebitis were noted in 3 cases (3,3%). Following external factors provoking venous thrombosis were identified in 19 patients (20,9%): lower leg injury in 14, high physical activity in 3, long flight in 1, recent coronavirus disease 2019 in 1. Median duration of thrombophlebitis manifestations was 6 days. Thrombosis was located in the trunk of the great saphenous vein in 96,7% of patients, while large tributaries were involved in 29,7%. The median distance from the thrombus proximal part to the saphenofemoral junction was 42,5 cm. Over 90±2 days, there were no cases of involvement of the suprafascial segment of the perforating vein in thrombosis to the fascia level, spread of thrombosis to the deep veins, or pulmonary embolism. Subsequently, a new episode of superficial vein thrombosis was noted only in 2 patients from the pharmacotherapy group with a history of thrombophlebitis.Conclusion. In patients with a low risk of venous thrombosis progression and predominantly distal location of acute ascending thrombophlebitis of the great saphenous vein and/or its large tributaries after endovenous laser ablation, progression of venous thrombosis is not expected over the next 3 months, despite an anticoagulation reduction to 7 days or its refusal.